The World Over - Under Capricorn : Art in the Age of Globalisation. - Curnow, Wystan; Fuchs, Rudi H.; Mignot, Dorine; Savage, Paula; Tillers, Imants; Wedde, Ian; City Gallery Wellington (Amsterdam : Stedelijk Museum Amsterdam, 1996)
Anderson, Laurie ; ART + COM ; Baumgarten, Lothar ; Byars, James Lee ; Dadson, Philip ; Delvoye, Wim ; Dibbets, Jan ; van Elk, Ger ; Grimonprez, Johan ; Intra, Giovanni ; Kaap, Gerald Van Der ; Killeen, Richard ; Kinoshita, Suchan ; Kleerebezem, Jouke ; McCahon, Colin ; Mullican, Matt ; Mirage, Merel ; Netband ; Paik, Nam June ; Parekowhai, Michael ; Scholte, Rob ; Schuil, Han ; Schum, Gerry ; Shanks, Janet ; Shaw, Jeffrey ; Simmons, Gary ; Smithson, Robert ; Struycken, Peter ; Tillers, Imants ; Tjapaltjarri, Clifford Possum ; Tremlett, David ; Viola, Bill ; Watson, Ruth
biografie, bibliografie
The World Over - Under Capricorn : Art in the Age of Globalisation, Stedelijk Museum Amsterdam, 29 juni tot 18 augustus 1996, City Gallery Wellington, June 6 - August 18, 1996
Engels
boek